Information System for the Secretariat Office of the Regional People's Representative Council (DPRD) of Bengkulu City Web-Based - Meyza Hani Putri; Indra Kanedi; Ricky Zulfiandry (Jurnal Media Computer Science, 2022)
Information is one of the important things in an agency, company, organization, institution and environment that is outside the system. The current Bengkulu City DPRD Secretariat in terms of finding information on the DPRD Secretariat data is still simple and there is no support system that can facilitate and search for data about employees, so we need a fast, precise and accurate system that can be useful for employees to find out administrative data and information. staff at the DPRD Secretariat. Therefore, the author intends to design a personnel information system at the Bengkulu City DPRD Secretariat. It is hoped that it can be used to find out information about the Bengkulu City DPRD Secretariat. This system is designed using MySQL Database and PHP Programming Language. And overall this information system can help users to find out information about the Bengkulu City DPRD Secretariat.